2023
DOI: 10.1002/mgg3.2154
|View full text |Cite
|
Sign up to set email alerts
|

A new patient with congenital myasthenic syndrome type 20 due to compound heterozygous missense SLC5A7 variants suggests trends in genotype–phenotype correlation

Abstract: Background Congenital myasthenic syndromes (CMSs) are characterized by hypotonia, episodic apnea, muscle weakness, ptosis and generalized fatigability. CMS type 20 (CMS20) is a rare disorder caused by variants in SLC5A7. In contrast to most other CMSs, CMS20 is also associated with neurodevelopmental disorders (NDDs). Only 19 patients from 14 families have been reported so far. Methods We studied a 12‐year‐old boy with symptoms manifested at six weeks of age. Later, he also showed speech delay, moderate intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…RNS tests were positive in the left common peroneal nerve, right tibial nerve, and left axillary nerve (deltoid muscle). Prior studies on six patients with SLC5A7 gene mutations [8][9][10] revealed significant reductions in low-frequency RNS in five cases. Only one case demonstrated a decrease in compound muscle action potential (CMAP) following 10 s of highfrequency RNS stimulation.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…RNS tests were positive in the left common peroneal nerve, right tibial nerve, and left axillary nerve (deltoid muscle). Prior studies on six patients with SLC5A7 gene mutations [8][9][10] revealed significant reductions in low-frequency RNS in five cases. Only one case demonstrated a decrease in compound muscle action potential (CMAP) following 10 s of highfrequency RNS stimulation.…”
Section: Discussionmentioning
confidence: 84%
“…2 qPCR verification for the patient's mother and brother in exon 1, 5, and 9 of the SLC5A7 gene excitability and led to low-potassium paralytic intestinal obstruction. Recurrent intestinal perforation has been documented in related literature [10]. Thus, it is hypothesized that cholinergic neurotransmission defects may significantly contribute to gastrointestinal motility disorders and gastric perforation in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations